Computational Screening of Heterocyclic L-Type Calcium Channel Blockers for Potential Anti-Parkinson’s Activity - Thomas Kurian; Rani Sebastian (Journal of Pharmaceutical Research, 2025)
Treating cardiovascular disorders like hypertension, arrhythmias, angina pectoris, and congestive heart failure involves using calcium channel blockers that bind allosterically to Cave L-type channels in myocytes in cardiac muscle. The heterocyclic compounds like 1, 4 dihydropyridines, phenyl alkyl amines, and benzodiazepines are calcium antagonists for cardiac diseases. The receptor protein CavAb in complex with Br- Verapamil was selected as a target for studying the interaction and prediction of calcium channel blocking activity of five heterocyclic compounds based on chemical structural features. using two popular software’s, Auto Dock and PyRx. The results predicted the activity of "2-(3, 4-methoxyphenyl)-5-(2, 2-phenylethylamine)-2-propan-2-ylpentanenitrile" and was chosen as the best score -6.9 – (strong) by auto dock and -9.8 by PyRX compared to the standard verapamil. Verapamil: - PyRX: -6.5, - Auto Dock: -5.22, Higher anticipated activity compounds (strong): 1. [(3R, 4S)-1-[2-ethyl (dimethylamine)]-4 (four-methoxyphenyl)5-dihydro-3H-1-benzazepin-3-yl, -7-methylsulfanyl-2-oxo-4] Acetate: - PyRX: -7.9, 2. 2-(3,4-ethoxyphenyl) - Auto Dock: -5.37(2) Phenyl ethylamine -5-2-propane-2-ylpentanenitrile:- PyRX: -9.8 molecules with weak estimated activity - Auto Dock: -6.251. 5-dicarboxylate, 4-dihydropyridine-3, 6-dimethyl-4-(3-nitrophenyl)-1, diethyl 2, PyRX: -7.2, 2. 4'- hydroxy-3'-methoxy acetophenone, Auto Dock: -3.81 PyRX: -5.6, Auto Dock: -4.31, 3. 1,4-dihydropyridine-3,5-dicarboxylate is diethyl 2,6-dimethyl-4-(4-nitrophenyl):PyRX: -6.8, Auto Dock: -4.52.Calcium channel blockers antiparkinson's effect is under recent global investigations. The ADME parameters studied for the compound were Inhibition of CYP1A2, BBB permeability, distribution, total clearance, oral rat acute toxicity (LD50), and toxicity with Swiss-ADME software. Lead optimization by identifying a molecule's salient characteristics will contribute to toxicity and building safer analogs.